DOES ENTREPRENEURIAL KNOWLEDGE MATTER FOR EDUPRENEURSHIP BEHAVIOR IN TEACHER TRAINING STUDENTS? - Puddin, Khafi; Dalimunthe, Muhammad Bukhori; Harahap, Lokot Muda; Rinaldi, Muammar; Prayogo, Rangga Restu; Panggabean, Fitri Yani (Assets: Jurnal Akuntansi dan Pendidikan, 2023)
ABSTRACTThis study aims to analyze the construct of the edupreneurship model for teacher training students. Questionnaires were given to students enrolled in the teacher training program at the Faculty of Economics, Universitas Negeri Medan, with a sampling of 275 respondents and an analytical tool for testing the relationship between variables using PLS-SEM. The empirical results found that attitude towards entrepreneurial knowledge proved to have no positive and significant effect; social support for entrepreneurial knowledge is proven to have a positive and significant impact; Self-efficacy on entrepreneurial knowledge is proven to have a positive and significant impact; entrepreneurial knowledge on edupreneurship behavior is proven to have a positive and significant effect.ABSTRAKPenelitian ini bertujuan untuk menganalisis konstruk model edupreneurship pada mahasiswa keguruan. Kuesioner diberikan kepada mahasiswa program keguruan Fakultas Ekonomi di Universitas Negeri Medan dengan total sampel sebanyak 275 responden dan alat analisis untuk menguji hubungan antar variabel menggunakan PLS-SEM. Hasil empiris menemukan bahwa sikap terhadap pengetahuan kewirausahaan terbukti tidak berpengaruh positif dan signifikan; dukungan sosial terhadap pengetahuan kewirausahaan terbukti berpengaruh positif dan signifikan; Efikasi diri terhadap pengetahuan kewirausahaan terbukti berpengaruh positif dan signifikan; Pengetahuan kewirausahaan terhadap perilaku edupreneurship berpengaruh positif dan signifikan.